Juneteenth Texas - Abernethy, Francis Edward; Project Muse. (University of North Texas Press, 1996)
Who were important in the collecting of African-American folklore, such as J. Mason Brewer; and a section giving resources for the further study of African Americans in Texas.
Juneteenth Texas reflects the many dimensions of African-American folklore. The personal essays are reminiscences about the past and are written from both black and white perspectives. They are followed by essays which classify and describe different aspects of African-American folk culture in Texas; studies of specific genres of folklore, such as songs and stories; studies of specific performers, such as Lightnin' Hopkins and Manse Lipscomb and of particular folklorists.
African-American folklore in Texas and in the Texas Folklore Society / Francis Edward Abernethy -- Black sacred harp singing remembered in East Texas / Donald R. Ross -- Henry Truvillion of the big thicket : a song worth singing / Jesse Truvillion -- Once upon a time in Houston's fourth ward / James Thomas Jackson -- Where the Cedar Grove / Clyde E. Daniels -- Mance Lipscomb : fight, flight or the blues / Glen alyn -- More than just 'possum'n taters : Texas-African foodways in the WPA slave narratives / T. Lindsay Baker -- Giving honor to God, the joy and salvation in my life : the appreciation service in song / Jan Rosenberg -- From gumbo to Grammys : the development of Zydeco music in Houston / Lorenzo Thomas -- From Behop to hard bop and beyond : the Texas jazz connection / Dave Oliphant -- African-American blacksmithing in east Texas / Richard Allen Burns -- Musical traditions of twentieth century African-American cowboys / Alan Govenar -- John Biggers, artist : traditional folkways of the black community / Alvia J. Wardlaw -- The African-American folktale and J. Mason Brewer / Lorenzo Thomas -- Juneteenth : a red spot day on the Texas calendar / William H. Wiggins, Jr. -- Lightnin' Hopkins : blues bard of the third ward / John Wheat -- "Bongo Joe" : a traditional street performer / Pat Mullen -- West African fiddles in deep east Texas / John Minton -- "The yellow rose of Texas" : a different cultural view / Trudier Harris -- The Texas trailblazer project / Patricia Smith Prather -- The Texas African-Americanphotography collection and archive / Alan Govenar -- The African-American Museum of Dallas / Alan Govenar.
Description based on print version record.
Keywords: Literatur; Afroamerikanische Musik; Folklore; African Americans -- Social life and customs; African Americans; Noirs americains -- Texas -- Moeurs et coutumes; Folklore -- Texas; Noirs americains -- Folklore -- Texas; Folklore -- Texas; African Americans -- Texas -- Social life and customs; African Americans -- Texas -- Folklore; African Americans -- Texas -- Social life and customs; Folklore -- Texas; African Americans -- Texas -- Folklore; Schwarze; Texas; Texas; Texas -- Folklore and legends; Folklore; Folklore; Electronic books